2001
DOI: 10.1054/bjoc.2001.1831
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of matrix metalloproteinase expression in primary and metastatic colon cancer: relationship to the tissue inhibitors of metalloproteinases and membrane type-1-matrix metalloproteinase

Abstract: The matrix metalloproteinases, MMP-2 and MMP-9, are capable of degrading components of the basement membrane, a vital barrier breached during the progression of colorectal cancer. The regulation of MMP-2 activation and subsequent targets is vital to understanding the metastatic process. MMP-2 was not expressed by colorectal cancer cells (C170 and C170HM 2 ) in vitro but by stromal fibroblasts (46BR.1GI). There was induction of this MMP upon transwell co-cultivation of the colon cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 23 publications
7
34
0
3
Order By: Relevance
“…The observed increase in MMP-2 expression observed in tumor samples is consistent with previous studies of breast (41,42), colon (43)(44)(45)(46)(47), stomach (48,49), lung (50 -53), rectal (43,54), and kidney cancer (55)(56)(57). Whereas a strong association of increased MMP-3 has been found in breast cancer (41, 58 -61), the increased expression levels observed in other tumor types are not as well supported by published literature.…”
Section: Sibling Expression and Tumor Progressionsupporting
confidence: 91%
“…The observed increase in MMP-2 expression observed in tumor samples is consistent with previous studies of breast (41,42), colon (43)(44)(45)(46)(47), stomach (48,49), lung (50 -53), rectal (43,54), and kidney cancer (55)(56)(57). Whereas a strong association of increased MMP-3 has been found in breast cancer (41, 58 -61), the increased expression levels observed in other tumor types are not as well supported by published literature.…”
Section: Sibling Expression and Tumor Progressionsupporting
confidence: 91%
“…High expression levels of MMP-2 in the malignant epithelium as well as in the surrounding stroma are associated with reduced survival of CRC patients (Collins et al, 2001). In the present study, MMP-2 mRNA was found to be up-regulated (10 times) in colorectal cancer tumor tissues compared to normal tissues (Figure 3).…”
Section: Discussionsupporting
confidence: 54%
“…Proteins were resolved under denaturing conditions, renatured for 1 hour, and incubated for 18 hours (37jC) in buffer containing 50 mmol/L Tris-HCl (pH 7.5), 150 mmol/L NaCl, and 5 mmol/L CaCl 2 . Gelatinolytic activity was visualized by Coomassie blue staining and quantified by densitometry (15,19). Where indicated, the tissue inhibitor of matrix metalloproteinase 1 (TIMP-1; Chemicon International) was dissolved in PBS and included in incubations.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, MMP-9 expression has been localized in the tumor stroma, mainly in fibroblasts and inflammatory cells (15,16). Thus, the current paradigm suggests that cancer cells stimulate stromal fibroblasts (17) and tumor-infiltrating inflammatory cells (18,19) to secrete MMP-9, which in turn contributes to the metastatic activity of the cancer cells. In this model, cancer cells exploit a physiologic mechanism for their metastatic dissemination because stromal cell MMP-9 is central to inflammation (20) and wound healing (21,22).…”
mentioning
confidence: 99%